The Effectiveness of the Kamsel Safety Riding Unit in Reducing the Number of Traffic Accidents Among Students at the Lamongan Police - Iskandar, Muh.Faldi (Indonesian Journal of Police Studies, 2024)
This research was motivated by the high number of traffic accidents in Lamongan Regency. The Traffic Unit in this case the Kamsel Unit has carried out Safety Riding Program activities in minimizing the number of traffic accidents among students. However, traffic accidents still occur frequently, this makes the author interested in researching the problem of how effective the safety riding unit kamsel in minimizing the number of traffic accidents among students. This study aims to describe the effectiveness of safety riding and describe the Safety Riding Program in minimizing the number of traffic accidents among Lamongan Police students. This research approach uses a qualitative approach, with data collection techniques of interviews, observations and document studies. Meanwhile, the validity and reliability techniques of the research data use data triangulation techniques using data analysis in the form of data reduction, data presentation, as well as drawing conclusions and verifying data. The concepts used are the concept of Traffic Accidents, Public Education, effectiveness using management theory, SWOT analysis theory, and AIDA theory Based on the results of this study that (1) The performance of the Kamsel Unit in minimizing the number of traffic accidents needs to be effective through the addition of Kamsel Unit personnel, completing facilities and infrastructure, and updating implementation methods. The author provides monthly evaluation suggestions, guided PKS training, student arrest patrols, kamsel-teacher groups, kamsel ambassadors. (2) The Safety Riding Program in preventing traffic accidents has not been effective, therefore it is necessary to improve activity planning, activity implementation, and supervision in the implementation of Safety Riding activities. The author concludes that the increase in traffic accidents is caused by several internal factors, namely activity planning, personnel organization, activity implementation, and personnel supervision. While external factors are still low level of public knowledge and lack of understanding about Safety Riding. However, this Safety Ridding program has not been implemented evenly to all students.